A Retrospective Comparison of MRI and Manual Inversion Stress Radiograph Studies in the Diagnosis of Chronic Lateral Ankle Instability. Issue 4 (16th October 2019) - Huggins, Pearson; Long, Joseph; Yancey, Conner; Rabe, Adam; Whitehead, Brent; Cheney, Nicholas; Law, Timothy; Schimmoeller, Kaitlyn
Category: Ankle, Sports Introduction/Purpose: Chronic lateral ankle instability (LAI) is a common cause of ankle pain. Surgical interventions have been shown to be highly effective in alleviating patient's symptoms once conservative care has failed. Stress radiographs have not demonstrated a clear efficacy in diagnosing ankle instability. Currently, MRI is considered to be superior to stress radiographs in the available literature. Unfortunately, the literature comparing these methods is limited. The purpose of this study is to compare the results of an MRI and manual inversion stress radiographs, in order to assess the accuracy of each modality in assessing the lateral ankle ligament competence. We believe that stress radiographs may have more value in confirming chronic ankle instability than the more expensive MRI imaging. Methods: A retrospective chart review was performed between January 2016 - July 2018 for patients diagnosed with LAI. The review identified 318 cases, of which 57 met the study criteria of having both an AP manual inversion stress radiographs, assessed by the senior author, and MRI, interpreted by a musculoskeletal radiologist, occurring within 6 months of each other without an acute injury within 12 weeks of the first image. For the remaining 57 cases, the imaging was reviewed in the following manner. For the MRI studies, the report was read from the radiologist assessing the lateral ankle complex. A positive MRI was denoted as pathology being reported by the radiologist. For the manual inversion stress radiograph, measurements were made to assess the degree of talar tilt while being stressed. A positive stress radiograph was identified based on asymmetry of the ankle joint during the stress. Results: The average time between imaging studies was 7.2±7.4 weeks (range 0.5-24 weeks). Of the 57 cases that qualified for the study, 43 (75%) had a positive stress radiograph, and 21(37%) had a positive MRI. 24 cases (42%) demonstrated a positive stress radiograph with a negative MRI, while 2 cases (4%) demonstrated a negative stress radiograph with a positive MRI. In respect to talar tilt, those patients identified as having a positive stress radiograph also had a higher average talar tilt when compared to those who did not. The degree of talar tilt for each set of criteria is summarized in Table 1. Conclusion: Historically, lateral ankle instability has been a clinical diagnosis. When further imaging is needed, our data suggests stress radiographs may demonstrate a higher reliability than MRI when assessing the competence of the lateral ankle ligaments. Asymmetry in a joint during an inversion stress examination has been shown to be indicative of multi ligament involvement. Few studies have attempted to define a talar tilt consistent with instability and our data does not meet those numbers. However, with the addition of bundled care and rising health care costs, we believe this provides a potential alternative in confirming a diagnosis of ankle instability.